Advances in the Treatment of Higher-Risk MDS: Current Strategies and Emerging Therapies - Stefani Parmentier (healthbook TIMES. Oncology Hematology)
Myelodysplastic syndromes/myelodysplastic neoplasms (MDS) are clonal hematopoietic stem cell disorders characterized by ineffective hematopoiesis, dysplasia of blood and bone marrow cells, and an elevated risk of progression to acute myeloid leukemia (AML). Patients with higher-risk MDS have a poorer prognosis, with up to 40% of them experiencing disease progression to AML within two years of diagnosis. Allogeneic stem cell transplantation (allo-SCT) remains the only potentially curative treatment for high-risk MDS. However, its use is limited by factors, such as patient age, comorbidities, cytogenetic profile, performance status, patient preference and donor availability. This article provides an overview of the therapeutic options for higher-risk MDS that are already established or in development, including hypomethylating agents, IDH1/IDH2 inhibitors, BCL2 inhibitors, RARA agonists, selective inhibitors of nuclear export, liposomal dual-drug chemotherapy and agents targeting aberrant inflammation. This review does not give detailed recommendations for single treatments.